A study on immunization practices amongst private medical practitioners of Bhopal city in central India - Mahra, G. D.; Pandey, Vikaas; Saxena, D. M.; Kaushal, Rituja (International Journal Of Community Medicine And Public Health, 2021)
Background: WHO advocates and highly recommend that National Immunization Programmes (NIPs) should increase collaboration and communication with private providers delivering vaccination services to ameliorate the purpose immunizing beneficiaries efficiently. Methods: It is a cross sectional observational study. It is done to assess immunization practices and other rel-evant aspects amongst private paediatrics practitioners of Bhopal city. Results: After doing appropriate statistical analysis, results revealed that most of the cold chain practices, vaccine administration practices, record keeping and reporting mechanisms were not up to the mark (i.e. p values < 0.05 at 95% confidence interval). However, training and level of experience contributed to improve in certain practice outcomes. Conclusions: Quality of immunization services in private sector could be enhanced by providing training and support to private immunization service providers.